2020
DOI: 10.3855/jidc.11707
|View full text |Cite
|
Sign up to set email alerts
|

Looking for NTDs in the skin; an entry door for offering patient centered holistic care

Abstract: Introduction: The majority of neglected tropical diseases (NTDs) have established primary skin manifestations or associated clinical feature. Skin NTDs often result in physical impairment and disfigurement, which can lead to disability. Skin diseases have been proposed as an entry point for integrated NTDs control. However, the magnitude and overlap of skin NTDs is poorly understood. Methodology: An institution-based cross-sectional study was done using medical records of dermatology patients between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
4
7
2
Order By: Relevance
“…However, a more pragmatic definition of skin NTDs typically refers to deep tissue or subcutaneous mycoses, such as mycetoma, rather than also including the superficial fungal diseases like ringworm. A study in Ethiopia found a fungal infection prevalence of 21.1% [12], a level that is similar to our findings. A study in Benin reported a higher prevalence for fungal dermatoses of 49% [15].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 92%
See 1 more Smart Citation
“…However, a more pragmatic definition of skin NTDs typically refers to deep tissue or subcutaneous mycoses, such as mycetoma, rather than also including the superficial fungal diseases like ringworm. A study in Ethiopia found a fungal infection prevalence of 21.1% [12], a level that is similar to our findings. A study in Benin reported a higher prevalence for fungal dermatoses of 49% [15].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 92%
“…The prevalence of skin NTDs vary greatly by setting type (for example community, or institution) and by country. In our study, the prevalence of cutaneous NTDs was 7.5%, less than the 17.2% from an Ethiopian hospital study [12]. Many other studies have focused on a single, or small number of, NTDs, yet most of these diseases share some of the same risk factors, can be found concurrently in the same patient, and could arguably be more efficiently investigated…”
Section: Discussioncontrasting
confidence: 73%
“…13 A more pragmatic definition of skin NTDs typically refers to deep tissue or subcutaneous mycoses, such as mycetoma, rather than also including the superficial fungal diseases like ringworm. A study in Ethiopia found a fungal infection prevalence of 21.1%, 11 a level that is similar to our findings. A study in Benin reported a higher prevalence for fungal dermatoses of 49%.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the prevalence of cutaneous NTDs was 7.5%, less than the 17.2% from an Ethiopian hospital study. 11 Many other studies have focused on a single, or small number of, NTDs, yet most of these diseases share some of the same risk factors, can be found concurrently in the same patient, and could arguably be more efficiently investigated together. 1 Here, 3.1% of participants had two cutaneous NTDs at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…The Ethiopian NTD strategic plan currently does not include mycetoma, as data is needed to formulate a mycetoma control strategy. Even though Ethiopian mycetoma cases were mentioned in a few studies [8][9][10] a detailed description of mycetoma cases has never been reported from Ethiopia. Here, we report for the first time a detailed description of seven mycetoma cases from Boru Meda Hospital, North East Ethiopia.…”
Section: Introductionmentioning
confidence: 99%